Dynamic Assessment of Fluid Responsiveness in Surgical ICU Patients Through Stroke Volume Variation is Associated With Decreased Length of Stay and Costs: A Systematic Review and Meta-Analysis. (January 2020) - Dave, Chintan; Shen, Jennifer; Chaudhuri, Dipayan; Herritt, Brent; Fernando, Shannon M.; Reardon, Peter M.; Tanuseputro, Peter; Thavorn, Kednapa; Neilipovitz, David; Rosenberg, Erin; Kubelik, Dalibor; Kyeremanteng, Kwadwo
Static indices, such as the central venous pressure, have proven to be inaccurate predictors of fluid responsiveness. An emerging approach uses dynamic assessment of fluid responsiveness (FT-DYN), such as stroke volume variation (SVV) or surrogate dynamic variables, as more accurate measures of volume status. Recent work has demonstrated that goal-directed therapy guided by FT-DYN was associated with reduced intensive care unit (ICU) mortality; however, no study has specifically assessed this in surgical ICU patients. This study aimed to conduct a systematic review and meta-analysis on the impact of employing FT-DYN in the perioperative care of surgical ICU patients on length of stay in the ICU. As secondary objectives, we performed a cost analysis of FT-DYN and assessed the impact of FT-DYN versus standard care on hospital length of stay and mortality. We identified all randomized controlled trials (RCTs) through MEDLINE, EMBASE, and CENTRAL that examined adult patients in the ICU who were randomized to standard care or to FT-DYN from inception to September 2017. Two investigators independently reviewed search results, identified appropriate studies, and extracted data using standardized spreadsheets. A random effect meta-analysis was carried out. Eleven RCTs were included with a total of 1015 patients. The incorporation of FT-DYN through SVV in surgical patients led to shorter ICU length of stay (weighted mean difference [WMD], −1.43d; 95% confidence interval [CI], −2.09 to −0.78), shorter hospital length of stay (WMD, −1.96d; 95% CI, −2.34 to −1.59), and trended toward improved mortality (odds ratio, 0.55; 95% CI, 0.30-1.03). There was a decrease in daily ICU-related costs per patient for those who received FT-DYN in the perioperative period (WMD, US −1619; 95% CI, −2173.68 to −1063.26). Incorporation of FT-DYN through SVV in the perioperative care of surgical ICU patients is associated with decreased ICU length of stay, hospital length of stay, and ICU costs.